Impact of motivational interviewing on outcomes of an adolescent obesity treatment: results from the MI Values randomized controlled pilot trial. Issue 5 (21st June 2018) - Bean, M. K.; Ingersoll, K. S.; Powell, P.; Stern, M.; Evans, R. K.; Wickham, E. P.; Mazzeo, S. E.
Summary: The aim of this study is to examine outcomes from MI Values, a motivational interviewing (MI) intervention implemented adjunctive to obesity treatment. Adolescents ( n = 99; 73% African American; 74% female; mean body mass index [BMI] percentile = 98.9 ± 1.2) were randomized to receive two MI sessions or education control. All adolescents participated in structured behavioural weight management treatment. Baseline, 3‐ and 6‐month assessments of anthropometrics, dietary intake and physical activity were obtained. Both groups had significant reductions in BMI z ‐scores and energy intake and increased physical activity at 3 and 6 months ( P < 0.05). MI participants reported greater reductions in 3‐month energy intake compared with controls. Participation in MI is associated with reduction in energy intake, consistent with better adherence to dietitian visits previously reported from MI Values. MI might be an effective adjunct to adolescent obesity treatment; future research is needed to determine if motivational interviewing can enhance BMI outcomes, via greater adherence to behavioural intervention.